S105 Pneumococcal serotypes implicated in adult pneumococcal pneumonia, 9 years following the introduction of the infant vaccine programme in the uk. (15th November 2016) - Daniel, P; Ashton, D; Sheppard, C; Eletu, S; Sandu, P; Litt, D; Fry, N; Lim, WS
Abstract : Background: The introduction of the pneumococcal conjugate vaccines into infant vaccination schedules, has led to a change in the serotype prevalence causing adult pneumococcal disease, through the process of herd immunity. Whilst there are national surveillance programmes informing the changes in serotype in invasive pneumococcal disease, there are no comparable data to demonstrate the ongoing vaccine effect on non-invasive pneumococcal community acquired pneumonia (CAP), the most common clinical manifestation of pneumococcal disease in adults. Methods: Consecutive adult patients admitted to 2 hospitals, covering the catchment area of a large UK city, with a diagnosis of CAP were studied prospectively, over a 1 year period between September 2014 and 2015. A novel multiplex assay capable of detecting 24 serotypes/serogroups of Streptococcus pneumoniae was performed on patient urine. Pneumococcal infection was determined by identification of the organism from either sterile sites and/or detection of pneumococcal antigen or serotype in urine samples. Results: Of 478 individuals admitted with CAP, pneumococcal disease was diagnosed in 166 (34.7%) cases. Pneumococcal CAP diagnosis was made by blood culture, pneumococcal urinary antigen detection and urinary serotype detection in 23 (13.9%), 61 (36.8%) and 149 (89.8%) cases respectively. A definitive single serotype was identified in 116 individuals; the most commonly observed were serotypes 3 and 8 (31 cases each, 26.7%), followed by serogroup 15 (14 cases, 12.1%), 17F (10 cases, 8.6%) and 33A/B/D/E (9 cases, 7.8%). Conclusion: This is the first report on extended serotype distribution implicated in adult pneumococcal CAP, 9 years after the introduction of the UK infant vaccination programme. In this era of high infant vaccine coverage, whilst the majority of isolates are non-vaccine types due to the effects of serotype replacement, serotype 3 remains a common cause of adult pneumococcal CAP and may reflect inadequate serotype specific vaccine effectiveness.